The influence of gender stereotyping and issue advocacy in advertising on consumer sentiment - Lucka, Nina Sissel (2020)
The purpose of this thesis is to explore the effect of the stimuli gender stereotyping and issue advocacy on consumer sentiment towards advertising and brand. In an experimental study, consumer groups are exposed to the two stimuli “gender stereotyping” and “issue advocacy” to understand their effect on consumers’ sentiment. The results indicate that issue advocacy can lift the negative effect of traditional female stereotyping. They further show that demographics are not necessarily the reason why a person favors or condemns stereotyping as well as advertising. On the contrary, it is far more linked to the personal disposition. The findings might encourage marketers to create advertising that allows the brand to connect better with its audience. While issue advocacy is currently trending, there has not been a lot of research on its effect on consumers. On contrary, gender stereotyping is frequently used, but has caused huge backlashes in recent ad campaigns. Thus, the paper hopes to enable marketers to better use these stimuli in order to achieve their desired outcome. The paper adds to the discussion of the use of stereotyping in advertising as well as the use of issue advocacy. It challenges the idea, whether brand-unrelated issue advocacy advertising and gender stereotyping is harmful for a brand.